Plant-based veterinary practices in Jammu and Kashmir: A review of the trends, transfer and conservation of traditional ethnoveterinary knowledge - Dutta, Abhishek; Sharma, Yash Pal; Bikarma, Bikarma Singh; Bussmann, Rainer W. (Ethnobotany Research and Applications, 2022)
Background: Traditional veterinary phytotherapy refers to the use of plants for promoting health and curing diseases of livestock. Animal rearing is the major occupation of the tribal communities in Jammu and Kashmir and is thus an important part of their economy. Due to the inaccessibility of modern facilities and allopathic drugs, these communities mainly rely on the local flora to cure common ailments prevalent in livestock, developing a rich knowledge of ethnoveterinary practices. These practices are still prevalent despite the advent of modern allopathic drugs as they are easily accessible, effective, and economic. To date, a plethora of studies have been carried out on ethnoveterinary plants in different regions of India, however few of these are available in Jammu and Kashmir itself. The aim of this review was to collate and analyze the traditional phyto-remedies against livestock ailments in Jammu and Kashmir. Methods: An extensive review of the published literature was carried out using various online databases like Academia, Google Scholar, PubMed, Researchgate, Sci-Finder, Scopus, Science direct, and other allied published literature. Results: A total of 18 research articles from the year 1989-2021 were selected which were exclusively related to the ethnoveterinary importance of plants. It was found that Jammu province was explored more as compared to Kashmir, as 10 studies were exclusively done from Jammu province and major attention was given to the ailments of cattle, sheep, and goats. Conclusion: The present review indicates that the medicinal plants reported need detailed biochemical assays to ascertain their therapeutical profiles that can contribute to the discovery of novel compounds to the existing drug pool. The integration of the reported plants into the biodiversity registers and promotion of this traditional heritage by the concerned government institutions and stakeholders involved in conservation is the utmost need of the hour which will ultimately result in the conservation of both the traditional knowledge and biodiversity. Keywords: Ethnoveterinary, Jammu and Kashmir, tribal, livestock, phyto-remedies